1996
DOI: 10.1016/s0022-5347(01)65644-1
|View full text |Cite
|
Sign up to set email alerts
|

Familial Transitional Cell Carcinoma

Abstract: Purpose: Bladder cancer is a common malignancy, and a frequent cause of urological consul tation and surgical intervention. Except for smoking and certain occupational exposures, the etiology of bladder cancer is largely unknown* Although the majority of patients with bladder cancer do not have a family history of transitional cell carcinoma of the urinary tract, the study of familial transitional cell carcinoma may lead to knowledge of the pathogenesis of this disease.Materials and Methods: To evaluate the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…The cardinal feature by which inherited predisposition is recognized clinically is family history. Genetic predisposition to bladder cancer was evident in a comprehensive review of familial bladder cancer (Kiemeney and Schoenberg, 1996), and a significant familial component in lung cancer was indicated using segregation analysis (Sellers et al, 1994). Gene-environment interactions have been associated with numerous tobacco-related cancer risks (Shields and Harris, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The cardinal feature by which inherited predisposition is recognized clinically is family history. Genetic predisposition to bladder cancer was evident in a comprehensive review of familial bladder cancer (Kiemeney and Schoenberg, 1996), and a significant familial component in lung cancer was indicated using segregation analysis (Sellers et al, 1994). Gene-environment interactions have been associated with numerous tobacco-related cancer risks (Shields and Harris, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Hereditary factors also contribute to the development of UUC with a 2-fold increased risk among first-degree relatives [3]. The familial cases develop due to site-specific inheritance as well as within the hereditary nonpolyposis colorectal cancer (HNPCC) syndrome [1,3-5]. Individuals with HNPCC are at increased risk for several types of cancer, with the highest life-time risks for colorectal cancer (80%), endometrial cancer (40–60%), ovarian cancer (10–15%), cancer of the small intestine and upper urothelial cancer [4], and the revised Amsterdam criteria for the diagnosis of HNPCC consider these tumor types to be associated with the syndrome [6].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Ilić et al found that bladder cancer risk was linked with the existence of familial bladder cancer, especially among the < 45 patients (RR = 1.45) and patients who smoked cigarettes (RR = 10.7)[60]. However, the prevalence of bladder cancer was 10% in the second-degree and third-degree relatives, and 3% in the first-degree relatives, suggesting that bladder cancer may not be a hereditary type of cancer[61]. Combined data from the Swedish, Danish, and Finnish twin registries revealed statistically significant effects of heritable factors for colorectal, breast and prostate cancer, ranging 27%-42%, but no significant association was observed in bladder cancer[62].…”
Section: Genetic Factorsmentioning
confidence: 99%